2019
DOI: 10.1038/s41398-019-0458-x
|View full text |Cite
|
Sign up to set email alerts
|

Protracted amygdalar response predicts efficacy of a computer-based intervention targeting attentional patterns in transdiagnostic clinical anxiety

Abstract: Individuals with clinical anxiety demonstrate an attention bias toward threatening information, which is thought to be partially driven by heightened amygdala activity to perceived threat. Attention Bias Modification (ABM) is a computer-based treatment that trains attention toward neutral stimuli and away from threatening stimuli. Alterations in initial processing of threat have been linked to ABM responses, but the impact of protracted processing in the aftermath of neutral and threatening information on ABM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 39 publications
(63 reference statements)
1
8
0
Order By: Relevance
“…Separate models were run for pupillary response for each emotion and epoch condition for several reasons. First, regression‐based analyses that examine valence or epoch effects separately can provide useful information regarding cognitive–affective processing biases relevant to ABM efficacy (Beevers, Clasen, Enock, & Schnyer, 2015; Kret et al., 2013; Price et al., 2018; Woody et al., 2019). Second, this approach reduces the statistical assumptions and complexity required of HLM models and also allows for easier comparisons with a previous publication from the project, which utilized HLM (Price et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Separate models were run for pupillary response for each emotion and epoch condition for several reasons. First, regression‐based analyses that examine valence or epoch effects separately can provide useful information regarding cognitive–affective processing biases relevant to ABM efficacy (Beevers, Clasen, Enock, & Schnyer, 2015; Kret et al., 2013; Price et al., 2018; Woody et al., 2019). Second, this approach reduces the statistical assumptions and complexity required of HLM models and also allows for easier comparisons with a previous publication from the project, which utilized HLM (Price et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, some anxious individuals exhibit perseverative attention to threat during sustained stages of processing, which can maintain negative affect and worry (Brosschot, Gerin, & Thayer, 2006; Burkhouse, Woody, Owens, & Gibb, 2015; Price et al., 2013). Although biases at each stage of attentional processing are present simultaneously in many patients, the temporal stages of AB are posited as dissociable dimensions of threat processing that exert unique influences on the development and maintenance of anxious vigilance and possibly require distinct interventions (Price et al., 2018; Woody et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several lines of evidence implicate impaired habituation in social anxiety (SA): a prolonged habituation response, for example, in the amygdala, has been linked to inhibited temperament (Blackford, Allen, Cowan, & Avery, ; Blackford, Avery, Cowan, Shelton, & Zald, ; Schwartz, ; Schwartz et al, ), a stable trait which is considered to be a risk factor for SAD (Clauss, Avery, & Blackford, ; Clauss & Blackford, ); furthermore, a study in a community sample of young adults revealed slower neural habituation of neutral faces in individuals with higher levels of social fearfulness (Avery & Blackford, ). These findings are further supported by work in nonhuman primates with an anxious temperament (cf., Fox & Kalin, ), and a recent study demonstrating that a sustained amygdala response to neutral stimuli predicts a worse response to attention bias modification treatment in transdiagnostic clinical anxiety (Woody et al, ). Together, these observations support the link between impaired habituation and the vulnerability for SA.…”
Section: Introductionmentioning
confidence: 99%